2017
DOI: 10.21873/anticanres.12072
|View full text |Cite
|
Sign up to set email alerts
|

1α,25(OH)2D3 Analog, MART-10, Inhibits Neuroendocrine Tumor Cell Metastasis After VEGF-A Stimulation

Abstract: Our data indicate that MART-10 could be deemed a promising drug for PanNET treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…An in vitro study using RIN-m cells, a rat insulinoma cell line expressing VDR, demonstrated that the exposure to 1α,25-dihydroxyvitamin D3 [1α,25(OH) 2 D 3 ] or MART-10, a 1α,25(OH) 2 D 3 analog, inhibits cell growth by induction of cell-cycle arrest at G0/G1 phase and apoptosis [103]. The same group also demonstrated that both MART-10 and 1α,25(OH) 2 D 3 effectively inhibited VEGF-induced metastatic potential of RIN-m cells through reducing the epithelial-mesenchymal transition and F-actin, which plays a role in cell migration and invasion [104]. These studies suggest that vitamin D and its analogs might represent a promising regimen for the treatment of NET patients.…”
Section: Vitamin D In Gep-netmentioning
confidence: 99%
“…An in vitro study using RIN-m cells, a rat insulinoma cell line expressing VDR, demonstrated that the exposure to 1α,25-dihydroxyvitamin D3 [1α,25(OH) 2 D 3 ] or MART-10, a 1α,25(OH) 2 D 3 analog, inhibits cell growth by induction of cell-cycle arrest at G0/G1 phase and apoptosis [103]. The same group also demonstrated that both MART-10 and 1α,25(OH) 2 D 3 effectively inhibited VEGF-induced metastatic potential of RIN-m cells through reducing the epithelial-mesenchymal transition and F-actin, which plays a role in cell migration and invasion [104]. These studies suggest that vitamin D and its analogs might represent a promising regimen for the treatment of NET patients.…”
Section: Vitamin D In Gep-netmentioning
confidence: 99%